Perancangan Continuous Improvement Program – Suggestion System untuk Membantu Pencapaian Key Performance Indicator Pada PT. X - Imelda Putri Gunawan (Jurnal Titra, 2018)
PT. X is aware the importance of continuous improvement, therefore the HRD Division, in contrast, HR Project Department created a program called Continuous Improvement Program – Suggestion System (CIP-SS). This program is aimed at improvements starting from simple things based on the 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) culture. Continuous improvement are important to do as they will help the achievement of the Key Performance Indicator (KPI), which will ultimately assist the company in achieving its vision and mission. CIP-SS has been run from August 2017, but the participants are still lacking because there are still some departments with no participants. Improvements are made with the remake of SOP and forms, as well as the making of posters and held socialization. The number of employees who participate CIP-SS after the improvement increased from 163 to 233 participants, and the projects collected increased from 272 to 445 projects.